Les pêches de l’URSS dans l’Atlantique du Nord-Est et l’élargissement des zones de pêche exclusive - Carré, François (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1987)
After the last war, the USSR set it self to increase the development of its ocean fisheries from its two North-East Atlantic seaboards on the Barents Sea and the Baltic. With a modernized fleet and almost complete freedom on the seas, its catch increased six fold between 1950 and 1976, going from 0,4 to 2,5 million tons per year, and Soviet fishermen could be found roaming on all the seas bordering Europe. However, as from 1977, this expansion was fiercely curtailed when coastal nations, including the USSR, established the 200-mile exclusive economic zone (EEZ) or mere exclusive fishing zone (EFZ), each being alloted almost all of its living resource s. More fishing grounds were lost by the USSR than gained, to the point where production suddenly fell in 1977 and it had to turn to fish of lesser quality, often used for industrial purposes, such as the Capelin (Mallotus villosus) and the blue Whiting (Micromesistius poutassou) which today make up to 60 % of all its catch off Northern Europe. The Soviet authorities reacted with flexibility and diversity, namely by increased fishing in the national exclusive zone, particularly in the Barents Sea, through negotiations leading to access rights to foreign waters, particularly those of Norway and the Faeroe Islands, and through a policy whereby it could purchase unprocessed fish from some members of the EEC. Thus Russian factory ships came to the British coasts to process mackerel delivered to them at sea by English and Scottish fishermen. It is through such a strategy of diversification, various examples of which may be found around the world, that the Soviets have succeeded in regaining grounds lost in 1977 and in reaching an average production of 1,7 million tons from 1977 to 1983 in the North-East Atlantic, this being 3 to 4 % less than that of 1970-76, notwithstanding the few purchases of fish made directly at sea.